To purchase or not? Why consumers make economically (non-)sustainable consumption choices. (10th February 2018) - Hüttel, Alexandra; Ziesemer, Florence; Peyer, Mathias; Balderjahn, Ingo
Abstract: Although ecologically and socially responsible consumption helps to reduce the harmful effects of resource use for both nature and society, all types of consumption (whether green or fair) deplete valuable resources. At the same time, to maintain household financial sustainability, spending should not exceed a household's financial resources. Thus, economically sustainable consumption is related to the consumer's decision to not buy products and the disposition to forgo specific purchases. Based on a means-end chain approach, this study investigates consumer cognitive decision-making structures related to six distinct options for economically (non-)sustainable consumption. Whereas saving motives, waste concerns, and avoidance motivations support economically sustainable decisions, economically non-sustainable decision-making is directly linked to attaining overall life goals. By clustering respondents based on the elicited means-end chains, the study discloses four consumer groups with distinctive motivational structures. The study also reveals several obstacles to promoting economic sustainability, indicates methods to overcome such obstacles, and suggests avenues for future research. Highlights: Means-end chain based exploration of economically (non-)sustainable decision-making. Avoidance motivations (e.g., wastefulness) support economically sustainable choices. Approach motivations nurture economically non-sustainable decision-making. Segmentation of four consumer groups with distinct decision-making styles.